An integrated litmus test platform for low-background detection and photothermal inactivation of Salmonella typhimurium via HCR-urease signal amplification - Qing Kang; Tong Lin; Jingbo Jiao; Xinjun Du; Shuo Wang (Food Chemistry, 2026)

2,6-Dibromophenol inhibits fin regeneration in zebrafish larvae via Wnt-mediated immune cell recruitment - Yuhan Huang; Wenya Tie; Zijian Li; Nannan Wang; Jiayan Xiong; Li Lin; Yuan Kong; Yunyi Mo; Minting Li; Jianpeng Liu; Zhonghao Xiao; Weitao Hu; et al. (Fish & Shellfish Immunology, 2026)

Identification of extreme socioeconomic droughts considering heavy tailed distribution - Zonglin Zhou; Xinjun Tu; Yan Wang; Vijay P. Singh; Qingzhi Wen; Xiaohong Chen; Kairong Lin; Zhiyong Liu; Meixian Liu (Journal of Hydrology, 2026)

Spatially explicit nutritional landscapes couple with environmental variables to shape nekton distribution patterns - Na Zang; Wenjun Zheng; Bilin Liu; Shaoqin Wang; Xinjun Chen; Dongming Lin (Limnology and Oceanography, 2026)
Species distributions are traditionally explained by environmental gradients, yet the role of nutritional factors, particularly essential fatty acids (EFA), remains poorly understood. We test the hypothesis that zooplankton EFA form a nutritional landscape that couples with environmental variables to shape the biogeography of nekton. We integrated spatial data of zooplankton EFA (arachidonic acid (ARA, 20:4n‐6), eicosapentaenoic acid (EPA, 20:5n‐3), and docosahexaenoic acid (DHA, 22:6n‐3)) with environmental variables into joint species distribution models (JSDMs). We compared explanatory power across three model types: JSDM_Env (environmental variables only), JSDM_EFA (EFA variables only), and JSDM_EnvEFA (combined environmental and EFA variables). Spatial analysis revealed significant heterogeneity in EFA concentrations, with elevated levels of EPA and DHA concentrated in the northeastern region. Model results showed that both EFA and environmental variables were effective predictors of species distributions. The JSDM_EnvEFA model exhibited the greatest explanatory power (mean AUC = 0.96, mean R 2 = 0.40), with variance decomposition revealing that EFA explained more variance than environmental variables (EFA: 54%, environment: 32%). Notably, EPA contributed up to 37% of the total explained variance, surpassing the influence of sea surface temperature (14%). Incorporating EFA also changed the estimated strength of species associations, suggesting that co‐occurrence patterns may be shaped by shared nutritional dependencies. Our results demonstrate that EFA availability is as critical as environmental variables in determining nekton species distributions, which support the spatial coupling hypothesis, demonstrating that EFA landscapes couple with environmental variables to structure pelagic communities. These findings establish nutritional landscape as a critical dimension of marine biogeography, providing a novel framework for predicting community responses to global change.

A novel urban boundary layer model integrating lidar measurement and physical equation constraints - Yue Xu; Yi Yang; Xianfeng Yu; Baojun Bai; Kunbo Wen; Lijun Yuan; Xinjun Lin (Urban Climate, 2026)

Transferable prediction of TBM long-distance tunneling construction duration considering uncertainties in surrounding rock distribution and the evolution of tunneling efficiency - Jianming Zhang; Kebin Shi; Peixuan Lin; Lei Li; Qiyong Mao; Haibo Jiang; Xinjun Yan; Jingwei Gong (Tunnelling and Underground Space Technology, 2026)

The Evidence for Nekton Distribution Modulated by Plankton Abundance in the High Seas Area of Northwest Pacific During Summer Season - Na Zang; Dongming Lin; Yizhen Shan; Bilin Liu; Xinjun Chen (Fisheries Oceanography, 2026)
Deterministic biotic interactions and abiotic conditions define species distributions and abundance, with plankton underpinning food webs to spatially structure predator distributions through bottom‐up processes. However, characterizing the mechanism underlying species abundance formation in an oceanic system remains challenging. We applied piecewise structural equation models to examine plankton abundance and environmental conditions in nekton assembly, combined with joint species distribution models to investigate the distribution associations between nekton and plankton in the high‐seas area of northwest Pacific. Results revealed that nekton distribution (fish and squid) showed significant associations with plankton abundance, where zooplankton correlations markedly surpassed phytoplankton associations. The fluctuations of plankton abundance directly influence nekton abundance, whereas the effects of environmental conditions were mediated indirectly through effects on plankton. These findings affirm the primacy of plankton abundance in driving nekton distribution and advance understanding of how bottom‐up trophic pathways modulate nekton distribution dynamics in pelagic ecosystems.

Smartphone-assisted portable colorimetric detection of Salmonella based on a dual signal amplification mediated nanozyme cascade aptasensor - Qing Kang; Chenjing Ma; Yidi Liu; Xin Yu; Tong Lin; Jingbo Jiao; Yukun Huang; Shuo Wang; Xinjun Du (Food Bioscience, 2026)

Adsorption-diffusion of trace organics in Baijiu on porous Fe2O3 - Qianxi Jiang; Manjiao Chen; Xinjun Hu; Weiqiang Zhou; Fan Zhao; Liangliang Xie; Haili Yang; Jinlong Yu; Zhoujun Lin; Caihong Shen (Journal of Food Engineering, 2026)

Nanoparticles-based lateral flow immunochromatographic strip for detection of foodborne pathogen: A review - Silu Hou; Tong Lin; Ziyi Ding; Shuxin Cui; Yafei Cao; Jingbo Jiao; Qing Kang; Xinjun Du (Food Chemistry, 2025)

In Vitro Characterization and Identification of Potential Probiotic Yeasts Isolated from Zaopocu, a Traditional Fermented Dregs Vinegar from Hainan Island - Lin Huang; Yuan Wang; Keyan Zhong; Ziyuan Jiang; Hengkai Jia; Shuying Chen; Zhiyuan Zhao; Xinjun Chen (Probiotics and Antimicrobial Proteins, 2025)

Designing of high-performance species habitat suitability index model - Huihui Zhang; Chunde Zhao; Jintao Wang; Xinjun Chen; Lin Lei (Fisheries Research, 2025)

Real-traffic emissions of CO, NOx, CO2, and PM2.5 from vehicles using a portable emission measurement system - Chunying Lu; Shuwei Dong; Shanqian Huang; Shuohan Gao; Jinsheng Fu; Xinyi Tian; Sha Lin; Xinzhu Xiong; Xinjun Wang; Xinfeng Wang (Air Quality, Atmosphere & Health, 2025)

Postharvest ripening improves the texture and active ingredients of noni fruit (Morinda citrifolia L.) for processing - Ruiqi Zhang; Qiongping Hong; Dengcheng Li; Lijuan Zhou; Xinjun Wang; Ruimin Wang; Sixin Liu; Lin Zhang; Congfa Li (Postharvest Biology and Technology, 2024)

Uncovering the impact of climate and vegetation changes on runoff in karstic regions of southwest China - Wei Luo; Meixian Liu; Zeyu Yao; Xinjun Tu; Kairong Lin (Journal of Environmental Management, 2024)

A framework for water supply regulation in coastal areas by avoiding saltwater withdrawal considering upstream streamflow distribution - Haiou Wu; Xinjun Tu; Xiaohong Chen; Vijay P. Singh; Leonardo Alfonso; Kairong Lin; Zhiyong Liu; Rongbiao Lai (Science of The Total Environment, 2023)

Drought prediction: Insights from the fusion of LSTM and multi-source factors - Tian Wang; Xinjun Tu; Vijay P. Singh; Xiaohong Chen; Kairong Lin; Zonglin Zhou (Science of The Total Environment, 2023)

Identification of Fishing State of Purse Seine Fishing Vessels Based on Multi-Indices - Zhenqi Xu; Jintao Wang; Cheng Zhou; Lin Lei; Xinjun Chen; Bin Li (Journal of Ocean University of China, 2023)

Correction to: Antioxidative effects of polypyrimidine tract-binding protein-associated splicing factor against pathological retinal angiogenesis through promotion of mitochondrial function - Lijie Dong; Tingting Lin; Wenbo Li; Yaru Hong; Xinjun Ren; YiFeng Ke; Xiaomin Zhang; Xiaorong Li (Journal of Molecular Medicine, 2023)

Retraction Note: Antioxidative effects of polypyrimidine tract-binding protein-associated splicing factor against pathological retinal angiogenesis through promotion of mitochondrial function - Lijie Dong; Tingting Lin; Wenbo Li; Yaru Hong; Xinjun Ren; YiFeng Ke; Xiaomin Zhang; Xiaorong Li (Journal of Molecular Medicine, 2023)

Spatial difference in feeding habits but similar foraging strategy for energy acquisition in jumbo squid - Yixuan Feng; Wei Song; Dongming Lin; André E. Punt; Xinjun Chen (Aquatic Ecology, 2023)

A CMIP6-based framework for propagation from meteorological and hydrological droughts to socioeconomic drought - Tian Wang; Xinjun Tu; Vijay P Singh; Xiaohong Chen; Kairong Lin; Zonglin Zhou; Jinglei Zhu (Journal of Hydrology, 2023)

Bivariate socioeconomic drought assessment based on a hybrid framework and impact of human activities - Zonglin Zhou; Xinjun Tu; Tian Wang; Vijay P. Singh; Xiaohong Chen; Kairong Lin (Journal of Cleaner Production, 2023)

Pexidartinib hydrochloride exposure induces developmental toxicity and immunotoxicity in zebrafish embryos via activation of Wnt signaling - Fasheng Liu; Hongmei Hu; Guilan Chen; Yanqi Lin; Wei Li; Ziyi Liu; Chao Chen; Xue Li; Sujie Sun; Li Zhang; Dou Yang; Kangyu Liu; et al. (Fish & Shellfish Immunology, 2023)

Individual diet specialization in the female jumbo squid Dosidicus gigas - Yixuan Feng; Kai Zhu; Dongming Lin; Xinjun Chen (Marine Biology, 2023)

Exploring the fungal communities and their correlation with the physicochemical properties of Zaopocu, a distinctive fermented food on Hainan island - Lin Huang; Yalin Han; Keyan Zhong; Xinjun Chen (Biologia, 2023)

Assessment of future socioeconomic drought based on CMIP6: evolution, driving factors and propagation - Tian Wang; Xinjun Tu; Vijay P. Singh; Xiaohong Chen; Kairong Lin; Zonglin Zhou; Yin Tan (Journal of Hydrology, 2023)

Stable isotope evidence for a shift in diet with increasing energy demand for reproduction in squid Illex argentinus - Wei Song; Yixuan Feng; Dongming Lin; Xinjun Chen (Hydrobiologia, 2023)

Form identification of purple flying squid (Sthenoteuthis oualaniensis) based on gladius morphology - Kai Zhu; Dongming Lin; Xinjun Chen; Kaida Xu (Frontiers in Marine Science, 2022)
Stock structure information is an important part of bases for understanding the dynamics of cephalopod populations. Purpleback flying squid Sthenoteuthis oualaniensis is an abundant and highly productive species in tropical and subtropical waters of the Indo-Pacific region. However, it is characterized by a complex stock structure, and the stock discrimination is an urgent priority to understand basic biology and for stock assessment and management purposes. Here, we used gladius morphology to identify and discriminate the dwarf without a dorsal photophore and middle-sized typical forms of S. oualaniensis in the South China Sea. Results showed that both forms had double axes on the gladius and females consistently had a larger gladius than males. Multivariate analyses using the gladius morphometric characteristics indicated that individuals of dwarf form without a dorsal photophore were distinguished from those of middle-sized typical form, which was evidenced by the obvious groups and significant dissimilarity of gladii of these two forms. The discrimination based on the gladius morphometric characteristics showed a high rate of accuracy, in which a global discrimination accuracy was estimated to be 92.36% for both forms without regarding sexes and 65.82% for the discrimination to form and sex. In combination, these lines of evidence indicated that individuals of dwarf without a dorsal photophore and middle-sized typical forms of S. oualaniensis can be accurately distinguished using the gladius morphometric characteristics, and these results will warrant the application of the gladius to study the stock structure of S. oualaniensis and other squid else.

Fatty Acid Profile of Jumbo Squid (Dosidicus gigas) off the Peruvian Exclusive Economic Zone: Revealing the Variability of Feeding Strategies - Guanyu Hu; Zhenfang Zhao; Bilin Liu; Dongming Lin; Jiawei Liang; Zhou Fang; Xinjun Chen (Fishes, 2022)
Jumbo squid Dosidicus gigas play a critical role in the marine ecosystems and are an important commercial species in the East Pacific. Generally, three size groups have been distinguished on the basis of the mantle length (ML) of an adult. Here, fatty acid (FA) analyses of muscle tissues were used to explore the feeding strategies of D. gigas off the Peruvian exclusive economic zone in terms of different size groups and sexes. There was no significant difference in fatty acid composition between the small- and medium-sized groups, whereas the large-sized group differed significantly from other groups. The higher content of C20:4n6 and (C18:2n6 + C18:3n3) indicates that the large-sized group may feed more frequently in nearshore and deep waters. Furthermore, the niches of the three size groups were consistent with the results of fatty acid composition, with the large-sized group occupying the widest trophic niche, followed by the medium-sized group and then the small-sized group. In addition, there was evidence of trophic niche overlap between the small and medium groups. In terms of sexual variability of the small and medium groups, the fatty acid composition significantly differed between females and males. In terms of sexual variation of the large group, the fatty acid composition between females and males was similar, indicating that similar feeding strategies may be adopted by them. This study revealed the variability of the feeding strategies of three size groups of D. gigas off the Peruvian exclusive economic zone.

Water Temperature at Different Depths Affects the Distribution of Neon Flying Squid (Ommastrephes bartramii) in the Northwest Pacific Ocean - Jintao Wang; Yiqi Cheng; Huajie Lu; Xinjun Chen; Lei Lin; Junbo Zhang (Frontiers in Marine Science, 2022)
Ommastrephes bartramii can vertically swim during its life, and previous studies have suggested the need to account for preferred habitat distribution influenced by water temperatures at different depths. To explore the impacts of deep-water temperature on O. bartramii spatial distribution, we constructed generalized additive models (GAMs) based on the Chinese squid-jigging fishery data and the Argo deep water temperature data during 2005–2018 in the Northwest Pacific Ocean to analyze the relationships between the local abundance of O. bartramii and deep-water temperatures. The results showed that the variables including surface water temperature ( T 0 ), water temperature at 30- and 100-m depths ( T 30 and T 100 ), and water differences between T 0 and T 30 ( D 0–30 ) significantly affected the spatial distribution of O. bartramii . The suitable ranges of each variable are different, > 15.5°C for T 0 , 11–18°C for T 30 , < 6°C for T 100 , and 4–4.5°C for D 0–30 . The areas occupied by the suitable T 30 seemed to reflect the outline of fishing ground, whereas the areas with suitable T 100 were to indicate the high density of O. bartramii . The predicted suitable habitat area and high-density area for O. bartramii are also regulated by El Niño–Southern Oscillation (ENSO) events. We demonstrated how the estimates of O. bartramii spatial distribution would vary influenced by deep-water temperatures in the Northwest Pacific Ocean. This information may help develop an appropriate method for investigating the effects of deep-water temperature on species with vertical migration.

Influence of environmental data of different sources on marine species habitat modeling: A case study for Ommastrephes bartramii in the Northwest Pacific Ocean - Lin Lei; Jintao Wang; Xinjun Chen (Acta Oceanologica Sinica, 2022)

Interannual Abundance Fluctuations of Two Oceanic Squids in the Pacific Ocean Can Be Evaluated Through Their Habitat Temperature Variabilities - Peng Chen; Xinjun Chen; Wei Yu; Dongming Lin (Frontiers in Marine Science, 2021)
Neon flying squid ( Ommastrephes bartramii ) and jumbo flying squid ( Dosidicus gigas ) are two commercially essential oceanic squids in the Pacific Ocean. An in-depth understanding of the mechanisms of their annual and interannual abundance fluctuations under environmental and climate variabilities can ensure ration and suitable management. Thus, the annual and interannual abundance fluctuations of the stock of the western winter-spring cohort of O. bartramii and D. gigas off Peru Exclusive Economic Zone (PEEZ) waters and their association with habitat temperature variabilities are explored in this study based on the historical Chinese Squid-jigging fishery data from 2003 to 2020. The habitat temperature variabilities were defined as the effective principal components of the SST at the squids’ two important habitats (spawning and feeding ground) through life histories according to the principal component analysis. The Hodrick—Prescott filter analysis was conducted to quantify the annual and interannual fluctuations of abundance and habitat temperature variabilities. Furthermore, the generalized additive model (GAM) was employed to investigate their associations. The results demonstrated different but not synchronous trends of abundance for O. bartramii and D. gigas . Regarding O. bartramii , the interannual abundance first decreased (2003∼2013) and then increased (after 2014). For D. gigas , the interannual abundance kept decreasing within 2003∼2020. Their annual trends have presented large fluctuations over years. The results of GAM indicated that using habitat temperature variabilities only can trace the abundance trend of O. bartramii and D. gigas at an interannual but not annual scale. Further studies verified that Pacific Decadal Oscillation (PDO) is a crucial factor affecting the interannual abundance trend of these two squids through the habitat temperature variabilities. However, this study indicates that the habitat temperature variabilities not only are related to other large-scale factors, which are not investigated currently at an interannual scale, but also, are combined with other small- or middle-scale factors at an annual scale on their impacts to the abundance fluctuations of these two squids. Therefore, in order to better explain the mechanisms of annual and interannual abundance fluctuations of O. bartramii and D. gigas under environmental and climate variabilities, the importance of combining other potential factors into consideration is highlighted.

RETRACTED ARTICLE: Antioxidative effects of polypyrimidine tract-binding protein-associated splicing factor against pathological retinal angiogenesis through promotion of mitochondrial function - Lijie Dong; Tingting Lin; Wenbo Li; Yaru Hong; Xinjun Ren; YiFeng Ke; Xiaomin Zhang; Xiaorong Li (Journal of Molecular Medicine, 2021)

Fatty acid composition and the evidence for mixed income–capital breeding in female Argentinean short-fin squid Illex argentinus - Dongming Lin; Fei Han; Sipeng Xuan; Xinjun Chen (Marine Biology, 2019)

regSNPs-splicing: a tool for prioritizing synonymous single-nucleotide substitution - Xinjun Zhang; Meng Li; Hai Lin; Xi Rao; Weixing Feng; Yuedong Yang; Matthew Mort; David N. Cooper; Yue Wang; Yadong Wang; Clark Wells; Yaoqi Zhou; et al. (Human Genetics, 2017)

Ovarian development in Argentinean shortfin squid Illex argentinus: group-synchrony for corroboration of intermittent spawning strategy - Dongming Lin; Xinjun Chen; Yong Chen; Guoping Zhu; Jizhou Yan (Hydrobiologia, 2017)

Considering the Order and Symmetry to Improve the Traditional RVA for Evaluation of Hydrologic Alteration of River Systems - Kairong Lin; Youqin Lin; Pan Liu; Yanhu He; Xinjun Tu (Water Resources Management, 2016)

Detection of potential fishing zones for neon flying squid based on remote-sensing data in the Northwest Pacific Ocean using an artificial neural network - Jintao Wang; Wei Yu; Xinjun Chen; Lin Lei; Yong Chen (International Journal of Remote Sensing, 2015)

Distribution of hotspots of chub mackerel based on remote-sensing data in coastal waters of China - Gang Li; Xinjun Chen; Lin Lei; Wenjiang Guan (International Journal of Remote Sensing, 2014)

Mineral Elements in the Hair of Amblyopic Children - QiaoLin Zhu; Jie Chen; MeiQin Zheng; Lin Chen; Jia Liu; JinFeng Tian; Wei Huang; XinJun Yang (Biological Trace Element Research, 2011)

Effects of water management and organic fertilization with SRI crop practices on hybrid rice performance and rhizosphere dynamics - Xianqing Lin; Defeng Zhu; Xinjun Lin (Paddy and Water Environment, 2011)